Aqueous Copper‐Mediated Living Radical Polymerisation of N‐Acryloylmorpholine, SET‐LRP in Water. Issue 10 (7th March 2014) - Anastasaki, Athina; Haddleton, Alice J.; Zhang, Qiang; Simula, Alexandre; Droesbeke, Martijn; Wilson, Paul; Haddleton, David M.
<x xml:space="preserve">Abstract</x> The polymerisation of N‐acryloylmorpholine in water is reported utilising Cu(0)‐mediated living radical polymerisation (SET‐LRP). The inherent instability of [CuI(Me6‐Tren)Br] in aqueous solution is exploited via rapid disproportionation to prepare Cu(0) particles and [CuII(Me6‐Tren)Br2] in situ prior to addition of monomer and initiator. Quantitative conversion is attained within 30 min for various degrees of polymerisation (DPn = 20–640) with SEC showing symmetrical narrow molecular weight distributions (Đ < 1.18) in all cases. Optimised conditions are subsequently applied for the preparation of a diblock copolymer poly(NIPAm)‐b‐(N‐acryloylmorpholine), illustrating the versatility of this approach. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>